The Historical Role of Islamic Trade in Building a Global Halal Economic Network in the Digital Era - Cahya, Melani Nur (Islamic Civilization and History, 2024)
Islamic trade has historically contributed to the global economic landscape, fostering trust, ethical practices, and a commitment to communal welfare. Today, these principles are foundational to the rapidly expanding halal economy, a market that transcends Muslim-majority regions and appeals to a global consumer base seeking ethical and sustainable products. This study aims to explore the role of Islamic trade history in shaping a cohesive global halal economic network within the digital era, focusing on how historical values can be integrated into modern digital practices. Using a qualitative descriptive approach, data were collected through document analysis, focusing on both historical records and contemporary halal market data. The findings show that principles of ethical transparency and communal benefit rooted in Islamic trade are essential for addressing modern digital marketplace challenges, such as product authenticity and consumer trust. Implementing digital tools, including blockchain and standardized certification, strengthens halal market integrity and enhances consumer confidence globally. The study highlights the importance of adopting these historically grounded principles to support sustainable growth and ethical practices in the halal economy.